Mitochondrial regulation in spermatogenesis. Issue 4 (24th February 2022) - Zhang, Zhaoran; Miao, Junru; Wang, Yuan
Abstract : The classic roles of mitochondria in energy production, metabolism, and apoptosis have been well defined. However, a growing body of evidence suggests that mitochondria are also active players in regulating stem cell fate decision and lineage commitment via signaling transduction, protein modification, and epigenetic modulations. This is particularly interesting for spermatogenesis, during which germ cells demonstrate changing metabolic requirements across various stages of development. It is increasingly recognized that proper male fertility depends on exquisitely controlled plasticity of mitochondrial features, activities, and functional states. The unique role of mitochondria in germ cell ncRNA processing further adds another layer of complexity to mitochondrial regulation during spermatogenesis. In this review, we will discuss potential regulatory mechanisms of how mitochondria swiftly reshape their features, activities, and functions to support critical germ cell fate transitions during spermatogenesis. In addition, we will also review recent findings of how mitochondrial regulators coordinate with germline proteins to participate in germ cell-specific activities.